Water Soluble Melanin Derivatives for Dynamic Contrast Enhanced Photoacoustic Imaging of Tumor Vasculature and Response to Antiangiogenic Therapy. Issue 1 (26th October 2016) - Longo, Dario L.; Stefania, Rachele; Callari, Chiara; De Rose, Francesco; Rolle, Riccardo; Conti, Laura; Consolino, Lorena; Arena, Francesca; Aime, Silvio
Abstract : A dynamic contrast enhanced (DCE) approach for tumor photoacoustic (PA) imaging is described. Novel water soluble melanin‐based derivatives are synthesized that exhibit good PA properties, stability, safety and accumulation in tumor bearing mice. This melanin derivative is capable to characterize tumor vasculature and to monitor vessel permeability changes upon antiangiogenic treatment. DCE‐PA imaging can assess functional response to cancer treatments.